Effects of different heating patterns on the decomposition behavior of white pine wood during slow pyrolysis - Wang, Yajun; Kang, Kang; Yao, Zonglu; Sun, Guotao; Qiu, Ling; Zhao, Lixin; Wang, Guan (International Journal of Agricultural and Biological Engineering, 2018)
This study investigated the effect of different heating rates on the pyrolysis behavior of the white pine wood residues. The raw materials were tested via two heating patterns with variable heating rates and compared with three other heating patterns with constant heating rates. The yields and characteristics of products such as char, pyrolysis oil and non-condensable gases under different heating rates were also determined. The gas, liquid, and solid phase yields of the products via heating with decreasing heating rates were similar to the yields obtained from constant heating rate at 2.3°C/min. The pyrolysis process by decreasing heating rates resulted in 30.04 % char, 44.53% bio-oil, and 25.43% non-condensable gases, which displayed higher char yield and pyrolysis gas than the other heating patterns. The results of thermo-gravimetric analysis showed that variable heating rate significantly changed the weight loss profiles during pyrolysis. It was observed during gas chromatography test that CO and CO2 were released earlier than CH4 and H2. The analysis of the chemical components confirmed that the bio-oil produced by heating process with decreasing rates contains less macromolecular organic matter content than the other patterns. Keywords: pyrolysis, variable heating rates, constant heating rate, product yields DOI: 10.25165/j.ijabe.20181105.3156 Citation: Wang Y J, Kang K, Yao Z L, Sun G T, Qiu L, Zhao L X, et al. Effects of different heating patterns on the decomposition behavior of white pine wood during slow pyrolysis. Int J Agric & Biol Eng, 2018; 11(5): 218–223.